Promotion Of Town Development Through Human Flow Simulation At Sports-Related Facilities - Shimizu, Ko; Nagasawa, Shinya; Shukuya, Mirei; Fujita, Kaede; Ichikawa, Manabu (Jurnal Manajemen Teknologi, 2025)
Abstract. In recent years, crowd congestion around large-scale sports facilities has emerged as a significant issue in urban safety and event management. This study evaluates the design and surrounding infrastructure of a planned new sports facility by simulating pedestrian flow using the Social Force Model and the S4 Simulation System. The facility, accommodating 15,000 people and located about 400 meters from the nearest train station, is expected to generate high post-event pedestrian volume. Nine simulation scenarios were tested by varying destination ratios and walking speeds based on age distribution. Results revealed that although average travel times remained similar across scenarios, significant differences in modal times and congestion points emerged depending on the agent distribution and routing assumptions. Key stagnation areas included the deck entrance and branching points within the facility. The study confirmed that while the basic design met safety requirements, inefficiencies in pedestrian flow—due to limited infrastructure and overly narrow walkways—hindered rapid dispersal. Based on the findings, the study recommends modifications to the infrastructure plan and plans for enhanced crowd guidance. The research findings underscore the importance of incorporating flow-based simulations into facility planning, contributing not only to visitor safety and satisfaction but also to data-driven urban development around large event venues. Keywords:  Pedestrian flow simulation, social force model, sports facility planning, urban infrastructure design, and post-event crowd management